Gender Mainstreaming as a Universal Tool for Constitution Writing: The Case of Iraq. (3rd May 2020) - Forman-Rabinovici, Aliza
Abstract: In light of postcolonial feminist criticisms, this article asks how does gender mainstreaming function as a strategy for introducing a gender perspective into the constitution writing process and constitutional text? The 2005 Iraqi Constitution is used to explore the method outside of its usual Western-dominated intergovernmental organization (IGO) context. Three main questions guide the analysis: Did gender mainstreaming promote gender equality effectively? Were there any shortcomings that were a result of a failure to account for intersectionality? Was the association of gender mainstreaming with Western-dominated IGOs a hindrance to the advancement of gender equality?